Analysis of depth of the microporosity in a nickel-chromium system alloy: effects of electrolytic, chemical and sandblasting etching - Neto, H. G.; Candido, MSM; Junior, ALR; Garcia, Patrícia Petromilli Nordi Sasso [UNESP] (Blackwell Publishing, 2003)
The present study was designed to analyse the average depth of the microporosity of a nickel-chromium (Ni-Cr) system alloy (Verabond II). The metal surface was subject to one of the following surface treatment: (i) Electrolytic etching in nitric acid 0.5 N at a current density of 250 mA cm(-2) ; (ii) chemical etching with CG-Etch etchant; and (iii) Sandblasting with alumina particles 50 mum. Half of the samples were polished before the surface treatments. The depth of porosity was measured through photomicrographs (500x) with a profilometer, and the data were statistically analysed using an analysis of variance (anova) followed by Tukey's test. The conclusions were (i) Differents surface treatment of the Ni-Cr system alloy lead to different depths of microporosity; (ii) the greatest depth of porosity was observed in non-polished alloy; (iii) the greatest and identical depth of microporosity was observed following electrolytic etching and chemical etching; (iv) the least and identical depth of microporosity was observed with chemical etching and sandblasting with alumina particles 50 mum, and (v) Chemical etching showed an intermediary depth.
Keywords: resin bonded bridge; electrolytic etching; chemical etching; sandblasting